Effect of the Zn/Ce ratio in Cu/ZnO–CeO2 catalysts on CO2 hydrogenation for methanol synthesis. (29th November 2021) - Chang, Shuai; Na, Wei; Zhang, Jiaqi; Lin, Lina; Gao, Wengui
Abstract : The addition of appropriate amounts of CeO2 to the Cu/ZnO–CeO2 catalyst can reduce the size of the Cu particles, increase the dispersion of Cu, reduce the reduction temperature and increase the concentration of basic sites and oxygen vacancies on the catalyst. Abstract : The hydrogenation of carbon dioxide to methanol is perceived as an effective way to mitigate global warming and drive fossil-fuel companies towards sustainable energy sources. In this study, a series of Cu/ZnO–CeO2 catalysts were prepared by a co-precipitation method, and the effect of the CeO2 content on the catalytic performance of the Cu/ZnO–CeO2 catalysts for the hydrogenation of CO2 to CH3 OH was analysed. The physicochemical properties of the catalysts were investigated using XRD, H2 -TPR, CO2 -TPD, BET, XPS, TEM, and DRIFTS. The CZC-3 catalyst (CZC stands for Cu/ZnO–CeO2 catalyst and 3 indicates a 30% CeO2 content) had the best catalytic activity at 280 °C in a 3 MPa CO2 /H2 (1/3) atmosphere, exhibiting a CO2 conversion rate of 15.6% and a methanol yield of 10.06%. More dispersed CuO species and oxygen vacancies were detected on the CZC-3 catalyst, leading to good activation of H2 and CO2, respectively. In situ DRIFTS results for the catalysts showed that the hydrogenation of CO2 to methanol over Cu/ZnO–CeO2 catalysts occurs via the formate pathway. The CeO2 -rich Cu/ZnO–CeO2 catalyst facilitated the conversion of formate to CH3 OH, and the presence of a large number of intermediate species on the surface of the CZC-3 catalyst greatly contributed to its catalytic performance for CO2 hydrogenation.